INFLUENCE OF INNOVATION ACTIVITY ON THE DEVELOPMENT OF AGRICULTURAL ENTERPRISES RESOURCE POTENTIAL (INNOVATIVE ECONOMY, 2020)
Misiuk М.V., Mushenyk І.М. INFLUENCE OF INNOVATION ACTIVITY ON THE DEVELOPMENT OF AGRICULTURAL ENTERPRISES RESOURCE POTENTIALPurpose.The purpose of the article is to analyze current state and trends in the agricultural enterprises development of innovative activities of Ukraine and the synthesis of directions and measures to increase their innovative activity.Methodology of research. In the process of writing the article, general scientific and special methods were used. The system and institutional approach is used to summarize the relationship of investment and innovation and the development of the agribusiness resource potential. The study used the following scientific methods: scientific abstraction – for theoretical synthesis, clarification of the conceptual apparatus on the study problem, the formulation of conclusions; statistical comparisons, in the index study of Ukraine competitiveness and investment and innovation support; the dialectical cognition method, which is used when considering the innovative development state of agribusiness; economic and mathematical – with the methodological approaches improvement to the innovative projects evaluation for the agricultural enterprises development.Findings. The formation theory basic principles of innovative activity on the resource potential development of agricultural enterprises are determined. The dynamics of the resource potential development of agricultural enterprises is substantiated. The theoretical and practical foundations of the innovation activities of the agro-industrial enterprises of Ukraine are considered. The problems that hamper the innovation activity of enterprises are covered. The priority directions of agro-industrial enterprises innovative development are indicated. Theoretical and methodological approaches to creating conditions for increasing the agricultural enterprises capacity for further innovative development are highlighted.Orinality. It consists in substantiating theoretical and methodological approaches and recommendations for improving the impact of innovation on the resource potential development of agricultural enterprises.Practical value. The research results can be used by the Kamianets-Podilskyi District State Administration in developing proposals and practical recommendations for substantiating the Plan for the Economic Development of Agriculture for 2018-2019.Key words: innovation; innovation activity; agro-industrial complex; agricultural enterprises.
Keywords: Key words; innovation; innovation activity; agro-industrial complex; agricultural enterprises.